Overproduction, purification and crystallization of PfTic22, a component of the import apparatus from the apicoplast of Plasmodium falciparum - Glaser, Stephanie (International Union of Crystallography, 2012)

(untitled)
Tic22 is a component of the protein-import apparatus of the chloroplasts of plants and algae and the apicoplasts of the Apicomplexa, a large group of organisms that includes the parasites that cause malaria. Tic22 is important for protein import into these organelles and for organelle biogenesis. It lies between the two membranes of chloroplasts, making interactions with components of both the TIC and TOC complexes. In the apicoplast, it is predicted to be located between the inner two membranes and to play a similar role in import. Although Tic22 is ubiquitous, its function is as yet uncertain. Tic22 from Plasmodium falciparum was therefore overproduced, purified and crystallized. A data set extending to 2.15 Å resolution has been collected from a crystal containing selenomethionine-labelled protein and structure determination is under way.